2020
DOI: 10.1016/j.eclinm.2020.100589
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing medical students’ choice of specialization: A gender based systematic review

Abstract: Background Students’ choice of medical specialties has evolved throughout year, with a growing interest in quality of life and in technological specialties. We investigated the repartition of such choices in the world and its influencing factors with a focus on the gender's influence, for helping policy-makers to deal with medical shortage and territorial to specialty disconnect. Methods A systematic search was conducted on MEDLINE and Scopus from January 2010 to Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
76
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 61 publications
(70 reference statements)
3
76
1
1
Order By: Relevance
“…This systematic review demonstrated that occidental women were more attracted to pediatrics than men (13.6% vs. 4.8%) [1] . Although stereotypically, females are portrayed as more nurturing and empathetic, this could be a misconception due to cultural expectations about gender roles [2] .…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…This systematic review demonstrated that occidental women were more attracted to pediatrics than men (13.6% vs. 4.8%) [1] . Although stereotypically, females are portrayed as more nurturing and empathetic, this could be a misconception due to cultural expectations about gender roles [2] .…”
mentioning
confidence: 87%
“…Analyzing gender's role in the career decision-making process of medical students would allow policy makers to develop strategies that ensure gender balance among specialties. Levaillant et al [1] . systematic review determined that males were mainly interested in surgery and internal medicine in both occidental (OC) and non-occidental (NOC) countries.…”
mentioning
confidence: 99%
“…Although women make up an estimated 70% of the global healthcare workforce, they are underrepresented in multiple distinct elds [11,12]. The gender variable has been associated with adverse implications while choosing the surgical eld, training for residency programs, and daily working in medical practice [13][14][15]. When appraising the intersections with minorities based on race, sexuality, and socioeconomic class, the gap expands [14,16,17].…”
Section: Policy Implicationsmentioning
confidence: 99%
“…The gender variable has been associated with adverse implications while choosing the surgical eld, training for residency programs, and daily working in medical practice [13][14][15]. When appraising the intersections with minorities based on race, sexuality, and socioeconomic class, the gap expands [14,16,17]. In this sense, GEIGS general assembly had capacity-building as a core value for its members and external participants.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…We thank Mayte Bryce-Alberti for her interest in our systematic review. In our paper [1] , we deliberately used the term “gender” and not “sex”, being more interested in cultural than biological differences. Moreover, most of the included studies collected data through survey, reflecting more the declared gender than the genetical sex.…”
mentioning
confidence: 99%